2017
DOI: 10.3389/fpsyg.2017.01488
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Time Pressure, Strategy Selection and Math Anxiety in Mathematics: A Review of the Literature

Abstract: We review how stress induction, time pressure manipulations and math anxiety can interfere with or modulate selection of problem-solving strategies (henceforth “strategy selection”) in arithmetical tasks. Nineteen relevant articles were identified, which contain references to strategy selection and time limit (or time manipulations), with some also discussing emotional aspects in mathematical outcomes. Few of these take cognitive processes such as working memory or executive functions into consideration. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 106 publications
3
50
1
Order By: Relevance
“…PS and MAT, and TSST which combines both tasks, are known to induce a significant cardiovascular and subjective stress response (Kirschbaum et al ., 1993; Westenberg et al ., 2009). The social-evaluative components including (false) feedback (Atchley et al ., 2017) and time pressure are particularly efficient in inducing stress (Dickerson and Kemeny, 2004; Caviola et al ., 2017). However, without subjective stress assessment, no clear conclusion can be drawn on the psychophysiological response to stress, thus limiting the findings of several of the studies reviewed here.…”
Section: Discussionmentioning
confidence: 99%
“…PS and MAT, and TSST which combines both tasks, are known to induce a significant cardiovascular and subjective stress response (Kirschbaum et al ., 1993; Westenberg et al ., 2009). The social-evaluative components including (false) feedback (Atchley et al ., 2017) and time pressure are particularly efficient in inducing stress (Dickerson and Kemeny, 2004; Caviola et al ., 2017). However, without subjective stress assessment, no clear conclusion can be drawn on the psychophysiological response to stress, thus limiting the findings of several of the studies reviewed here.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies it would be extremely interesting to no longer look at the relationship between these three variables, but rather the complete explanatory hypotheses, maybe designing longitudional or repeated measure studies that might adequately capture the causal relationships implicit in the two hypotheses. One recent study (Caviola et al, 2017) reviewed past research which looked at how stress induction, manipulation of time pressure, and math anxiety could interfere with and/or condition the selection of strategies to solve arithmetic problems. The researchers concluded that, owing to the scant available literature, the questions could only be partially answered, and currently there is not much evidence of clear associations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the task in the current study also involved basic operations of addition, subtraction, multiplication and division, it was performed under time pressure. Caviola et al (2017a) reviewed studies addressing the effects of time pressure on math performance and concluded that time pressure indeed affected math performance by choosing strategies that can be applied quickly but might be suboptimal. Gender related effects were not studied or reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has consistently been reported that higher levels of math anxiety are related to lower scores on math achievement tests, fewer math courses taken, lower grades in math courses, and to avoiding certain career paths involving mathematics (e.g., Ma, 1999; Ashcraft and Krause, 2007; Ashcraft and Moore, 2009). Math anxiety can be provoked by simple arithmetic problems when performing under time pressure (Ashcraft, 2002; Caviola et al, 2017a) and with increasing complexity of arithmetic tasks (Kellogg et al, 1999; Ashcraft and Krause, 2007). Although the relation between math anxiety and achievement in mathematics has been studied extensively in adults and adolescents, little research has focused on this relation in young children in elementary school (Ganley and McGraw, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation